LAJU INFILTRASI DAERAH KECAMATAN BUNGURSARI DAN SEKITARNYA DI KABUPATEN PURWAKARTA, PROVINSI JAWA BARAT: RATE OF INFILTRATION IN THE BUNGURSARI DISTRICT AND SURROUNDINGS IN PURWAKARTA DISTRICT, WEST JAVA PROVINCE - Assyidik, Ahmad Ikhsan; Amri, Muhammad Adimas (Journal of Geoscience Engineering and Energy, 2024)
The research area is in Bungursari District and the surrounding Purwakarta Regency. This research aims to determine the distribution of infiltration rate values in the research area. The method used is measuring soil infiltration using a double ring infiltrometer. Then it is known that the infiltration rate value is divided into 3 zones, namely, medium infiltration rate (2 – 6.5 cm/hour), fast infiltration rate (12.5 – 25 cm/hour), and very fast infiltration rate (>25 cm/hour).